2015
DOI: 10.1002/anie.201504834
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Gold Nanoparticle Stabilization by Acetylenic Phosphaalkenes

Abstract: Acetylenic phosphaalkenes (APAs) are used as a novel type of ligands for the stabilization of gold nanoparticles (AuNP). As demonstrated by a variety of experimental and analytical methods, both structural features of the APA, that is, the P=C as well as the C≡C units are essential for NP stabilization. The presence of intact APAs on the AuNP is demonstrated by surface-enhanced Raman spectroscopy (SERS), and first principle calculations indicate that bonding occurs most likely at defect sites on the Au surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…There are some case studies on kinetics of ligand adsorption to colloidal particles, which include (1D, 2D, continuous) nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR), UV/Vis spectroscopy, time‐correlated single photon counting spectroscopy (TCSPC), photoluminescence (PL), resonance elastic light scattering (RELS), and surface‐enhanced Raman scattering (SERS), as well as gas chromatography (GC) for the supernatant . However, all these strategies suffer from one or more of the following disadvantages: 1) the required assumption that the extremum of the signal corresponds to full coverage is not necessarily correct, as adsorption sites might be blocked by steric hindrance or ligands remaining from synthesis; 2) low time resolution; 3) no defined target property of functionalized NPs that can be quantitatively evaluated (most of the approaches are based on colloidal gold particles which have as a kind of fortunate singularity only one well‐defined surface plasmon resonance (SPR) peak); and 4) tedious sample preparation.…”
Section: Figurementioning
confidence: 99%
“…There are some case studies on kinetics of ligand adsorption to colloidal particles, which include (1D, 2D, continuous) nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR), UV/Vis spectroscopy, time‐correlated single photon counting spectroscopy (TCSPC), photoluminescence (PL), resonance elastic light scattering (RELS), and surface‐enhanced Raman scattering (SERS), as well as gas chromatography (GC) for the supernatant . However, all these strategies suffer from one or more of the following disadvantages: 1) the required assumption that the extremum of the signal corresponds to full coverage is not necessarily correct, as adsorption sites might be blocked by steric hindrance or ligands remaining from synthesis; 2) low time resolution; 3) no defined target property of functionalized NPs that can be quantitatively evaluated (most of the approaches are based on colloidal gold particles which have as a kind of fortunate singularity only one well‐defined surface plasmon resonance (SPR) peak); and 4) tedious sample preparation.…”
Section: Figurementioning
confidence: 99%
“…In comparable previous works, Ott and co‐workers intensively studied various alkynyl‐substituted phosphaethenes for the development of π‐extended phosphaethene derivatives . In a study of alkynyl‐substituted phosphaethenes, Ott et al found that the nucleophilic substitution reaction of bromophosphaethenyllithium [Mes*P=C(Br)Li] with sulfonylacetylenes afforded the corresponding 2‐bromo‐2‐alkynyl‐1‐phosphaethenes [Mes*P=C(Br)C≡CR], which underwent subsequent transformation and redox analyses , . In this work we have demonstrated an efficient catalytic process for the synthesis of various alkynyl‐substituted 2‐bromo‐1‐phosphaethenes by using 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Applications of these 7.9 to 9.8 nm AuNPs through functionalization with other ligand systemsw as also demonstrated. [116] Over the last years also phosphaalkyne-metal complexes have been investigated due to their potentials witch from side-on to endon coordination. Russell and co-workers reported, in aV T-NMR study,t he first cationic phosphine-supported phosphaalkyne-Au complex showingadynamic situation of free and coordinated Pc enters through an associative mechanism.…”
Section: Coordination Compounds Of Phosphaalkenes And-alkynesmentioning
confidence: 99%